The Use Of Gis And Resistivity Imaging Techniques To Determine Landslide Probability Based On Internal And External Causal Factors - Al-Musawi, Hussein Abdelwahab Moussa (2010)

(untitled)
The main objective of the study is to investigate the landslide probability map through internal and external causal factors. The most important internal causal factors of landslide (ICFL) are subsurface structure, groundwater, sliding subsurface and water movement whereas external causal factors of landslide (ECFL) are slope angle, aspect of the slope, elevation of the slope and the land cover. Part of Karak highway in Malaysia has been selected for the study due to frequent occurrences of landslide. A new integration between Resistivity Imaging (RI), and Geographic Information System (GIS) were carried out to study the landslide in the target area. The RI has been used to find out the ICFL whereas the GIS was used to present the factors. Theodolite and GPS were used to determine the ECFL. Digital Elevation Model (DEM) and GIS were used to map the ECFL. Before applying the RI to find out the ICFL, a new approach called Monitoring and Enhancing Accuracy of Resistivity Imaging (MEARI) was suggested to increase the efficiency of the RI. Moreover, a comparison between the most common conventional arrays has also been carried out to find out the most suitable array for the study.